Molecular Characterization of High-Risk Human Papillomavirus in Women in Bobo-Dioulasso, Burkina Faso. (20th July 2016) - Traore, Ina Marie Angèle; Zohoncon, Théodora Mahoukèdè; Dembele, Adama; Djigma, Florencia W.; Obiri-Yeboah, Dorcas; Traore, Germain; Bambara, Moussa; Ouedraogo, Charlemagne; Traore, Yves; Simpore, Jacques
Abstract : High-risk human papillomavirus (HPV) is found in over 99% of cervical cancers. The aim of this study was to determine the prevalence of HPV in a population of women in Bobo-Dioulasso and to identify the high-risk types present in these women. From May to June, 2015, 181 women who came for consultation at the Souro Sanou University Hospital of Bobo-Dioulasso have been included in this study. Uterine endocervical swabs have been taken in these women. DNA obtained by extraction from the samples thus collected was used to determine the prevalence of high-risk human papillomavirus genotypes through real-time PCR. The age of the women ranged from 20 to 56 years with a mean of 35.3 ± 8.1 years. The prevalence of infection by high-risk HPV types was 25.4% (46/181). The most common high-risk HPV genotypes were HPV 39 (18.5%), HPV 52 (16.7%), HPV 18 (14.8%), and HPV 35 (13.0%). HPV 16 which is included in the HPV vaccines was not found in the population studied. This type of study which is the first one in Bobo-Dioulasso has showed a high prevalence of genotypes HPV 39, HPV 52, and HPV 35 which are not yet covered by a vaccine.